Analysis of Student Learning Motivation Through The Predict, Observe, Explain (POE) Learning Model - Nisa Aulia Mahardika; Tri Ariani; Endang Lovisia (Equator Science Journal, 2024)
This study aims to determine how student learning motivation after applying the Predict, Observe and Explain (POE) learning model. The method used in this study is an experimental method with the population, namely students of SMA Negeri 2 Lubuklinggau class X. Based on the population, sampling is carried out in class X IPA 2 using the Simple Random Sampling technique because the sample is a randomly taken population. The instrument used is in the form of a motivation questionnaire from each student, where the test results will be seen based on motivation indicators and percentages. From the results of the analysis, 94% of students have very good motivation, 6% of students have good learning motivation, 0% of students have less learning motivation, and 0% of students have very less learning motivation. Based on the results of the analysis obtained, it can be concluded that after the implementation of the POE learning model students have high motivation to do physics learning. This can be seen in the percentage which in the table shows excellent and good data analysis.